Bioactive compounds of the Mediterranean diet and prostate cancer. (2nd October 2018) - López-Guarnido, Olga; Urquiza-Salvat, Noelia; Saiz, Maria; Lozano-Paniagua, David; Rodrigo, Lourdes; Pascual-Geler, Manrique; Lorente, Jose Antonio; Alvarez-Cubero, Maria Jesus; Rivas, Ana
Abstract: Objective: The purpose of this review is to examine the evidence on the effects of bioactive constituents of the Mediterranean diet (MeDi) on prostate cancer (PCa) risk. Methods: The search for articles came from extensive research in the following databases: PubMed, Scopus, and Web of Science. We used the search terms "Mediterranean diet, " "lycopene, " "vitamin E, " "vitamin C, " "Selenium, " "resveratrol, " "prostate cancer, " and combinations, such as "lycopene and prostate cancer" or "resveratrol and prostate cancer." Results: Numerous studies investigating the effect of various dietary nutrients on PCa have suggested that selenium is probably the most promising. Several studies reported reduced PCa risk associated with vitamin C and E intake, while other studies reported no association. Lycopene inhibits cell proliferation and inducts apoptosis, thus protecting against cancer. Also, it has been found in various in vivo and in vitro studies that resveratrol, inhibits PCa development. Conclusions: The high content of bioactive phytochemicals in the MeDi is of particular interest in the prevention of PCa. Further large-scale studies are required to clarify the effect of MeDi bioactive compounds on prostate health, in order to establish the role of this diet in the prevention of PCa.